Energy transition and environmental sustainability: the interplay with natural resource rents and trade openness - Qiang Wang; Xinhua Wang; Rongrong Li (Humanities & Social Sciences Communications)
Abstract Amid escalating global environmental challenges, sustainable development has become a critical priority, with energy transition playing a key role in reducing ecological degradation. This study investigates the connection between energy transition and environmental sustainability, with particular attention to its role in altering human demand on natural ecosystems. Leveraging a dataset that encompasses 162 countries over the period from 1990 to 2022, the research explores how shifting from carbon-intensive energy to renewable sources affects ecological outcomes. Additionally, it investigates how natural resource rents and trade openness may amplify or diminish the benefits of energy transition. Research findings suggest that shifting towards cleaner energy typically contributes to lowering environmental pressure, supporting long-term sustainability. However, the effectiveness of this transition is heavily influenced by external economic factors. Specifically, higher levels of natural resource rents and greater trade openness tend to weaken the positive environmental impacts of energy transition. The results underscore the importance of tailoring energy strategies to specific economic contexts, emphasizing an integrated framework that combines environmental goals with wider economic planning.